Fetal Infection by Zika Virus in the Third Trimester: Report of 2 Cases. (6th September 2016) - Soares de Souza, Antonio; Moraes Dias, Cristiane; Braga, Fernanda Del Campo Braojos; Terzian, Ana Carolina Bernardes; Estofolete, Cássia Fernanda; Oliani, Antonio Hélio; Oliveira, Gustavo Henrique; Brandão de Mattos, Cinara Cássia; de Mattos, Luiz Carlos; Nogueira, Maurício Lacerda; Vaz-Oliani, Denise Cristina Mós
Abstract: Zika virus (ZIKV) infection acquired during pregnancy is associated with congenital microcephaly. We describe 2 cases of ZIKV infection in women in their 36th week of pregnancy whose fetuses had preserved head circumference at birth and findings of subependymal cysts and lenticulostriate vasculopathy in postnatal imaging. These represent the first signs of congenital brain injury acquired due to ZIKV in the third trimester.